TEARING DOWN THE WALL BETWEEN THE UNIVERSITY AND THE SCHOOL: a word of the practice of the Institutional Scholarship Program Initiation to Teaching, PIBID - Moreira Calazães, Paula Cristina; Saldanha de Souza, Patrick Victor; Silva de Souza, Vinícius; de Freitas Paulo, Vitória Nara (PÓLEMOS – Revista de Estudantes de Filosofia da Universidade de Brasília, 2017)
The transversality of philosophy helps in the development of a more inclusive and interdisciplinary work proposal.Â Therefore, the teaching of philosophy today participates in the academic life of Brazilian basic education and its performance helps in the formation of future critical, participatory, questioning and afflicted citizens of knowledge. Seeking a dialogue between philosophical theories and high school students does not, therefore, present itself at first as an easy task, but rather as a challenging one. However, an aid tool for this challenge of teaching philosophy is the presence of the Institutional Scholarship Program for Teaching - PIBID, which ensures the participation of higher education within the schools of basic education.